Selection of Prosthesis in Aortic Valve Surgery: Short Review and Trend in our Practice in 10 Years - Selman Dumani; Ermal Likaj; Laureta Dibra; Devis Pellumbi; Adelina Musliu; Fjoralba Qejvani; Altin Veshti (Albanian Journal of Trauma and Emergency Surgery)
Introduction: In our country, the predominant condition treated in aortic valve surgery in its early stages was aortic valve disease of rheumatic origin, primarily in patients under the age of 60. In recent decades, due to lifestyle changes, increased average lifespan, and a shift in surgical treatment concepts among the elderly, there has been a noticeable trend towards atherosclerotic aortic valve disease treated surgically. This condition poses challenges in selecting the type of prosthesis for surgical replacement—either bioprosthetic or mechanical. The replacement of the aortic valve, aside from its undeniable benefits for patients, also introduces various complications, such as bleeding related to anticoagulation, thromboembolism, prosthetic endocarditis, and structural degeneration of the prosthesis. These complications vary between the two main groups of prostheses: bioprosthetic and mechanical. In this context, we are confronted with the challenge of selecting the type of prosthesis suitable for each patient.